PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA MATERI RUANG LINGKUP BIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 1 MUTIARA - Makawiyah, Makawiyah; Zuraida, Zuraida; Salbiah, Salbiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
Research with the title Application of the Inquiry Learning Model in Biology Scope Material to Improve Learners Learning Outcomes at SMA Negeri 1 Mutiara. This research aims to determine the improvement in learners' learning outcomes through the application of the inquiry learning model to biology scope material at SMA Negeri 1 Mutiara. The population is all learners of class X MIPA SMA N 1 Mutiara consisting of 6 classes with a total of 180 learners. Of the six classes by using a random sampling technique (random method) to determine the experimental class and control class. The data collection technique for this research is a test technique in the form of 25 multiple-choice questions. From the results of data analysis, it was obtained that tcountttable was 4.511.67 at a significance level of 0.05. Based on these data, the hypothesis formulated, namely that the application of the Inkuri learning model can increase learners ' understanding of learning concepts in biology scope material in class X SMA N 1 Mutiara, can be accepted as true.Keywords : Inquiry Learning Model, Learning Outcomes, Scope of Biology